2020
DOI: 10.37339/e-bis.v4i2.228
|View full text |Cite
|
Sign up to set email alerts
|

Efek Mediasi Literasi Keuangan Terhadap Hubungan Antara Kualitas Pembelajaran Keuangan dengan Keputusan Investasi

Abstract: Tujuan Penelitian ini untuk menguji Efek Mediasi Literasi keuangan Terhadap hubungan antara kualitas pembelajaran keuangan dengan keputusan investasi.Metode penelitian ini menggunakan pendekatan penelitian kuantitatif, bersifat deskriptif verifikatif. Sampel penelitian ini sebanyak 93 maasiswa yang telah mengikuti literasi keuangan, teknik sampling menggunakan purposive simple random sampling. Untuk menguji Efek Mediasi menggunakan Bootstrapping approach dengan bantuan SPSS versi 25 dan Process V3.4.Hasil pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
2
3
0
3
Order By: Relevance
“…Previous research found that Financial Behavior has a positive and significant effect on investment decisions (Mutiara & Agustian, 2020;Upadana & Herawati, 2020). Financial behavior was also found to fully mediate the relationship between financial literacy and investment decisions (Perwito et al, 2020). Based on this description, this study formulates hypotheses H2 and H3.…”
Section: H1: There Is a Significant Positive Association Between Fina...mentioning
confidence: 81%
“…Previous research found that Financial Behavior has a positive and significant effect on investment decisions (Mutiara & Agustian, 2020;Upadana & Herawati, 2020). Financial behavior was also found to fully mediate the relationship between financial literacy and investment decisions (Perwito et al, 2020). Based on this description, this study formulates hypotheses H2 and H3.…”
Section: H1: There Is a Significant Positive Association Between Fina...mentioning
confidence: 81%
“…untuk memperoleh keuntungan yang optimal serta memastikan keuangan perusahaan dalam keadaan stabil dan baik. Menurut (H. Chen & Volpe, 1998) maka Literasi Keuangan mencakup memahami pengetahuan dasar untuk keuangan pribadi, tabungan dan pinjaman, asuransi dan investasi (Perwito et al, 2020). Sementara menurut Nababan dan Sadalia, (2012) Bahwa Literasi Keuangan mencakup dasar keuangan pribadi, pengelolaan keuangan, pengelolaan kredit dan pinjaman, tabungan dan investasi, dan pengelolaan risiko.…”
Section: Literasi Keuanganunclassified
“…al ( 2022 Bhaskara (2017) and Putri & Rahyuda (2017) show that financial literacy has a significant positive effect on investment decisions. In research conducted by Ramadani et al (2022) and Perwito et al (2020) stated that financial literacy has a positive effect on investment decisions. On research conducted by Audini (2020); Baihaqqy et al (2020); Dewi & Krisnawati (2020) and Khairiyati & Krisnawati (2019) also proved that financial literacy has a significant effect on investment decisions.…”
Section: The Effect Of Financial Literacy On Investment Decisionsmentioning
confidence: 99%
“…al (2022); Chong et al (2021); Kurniawan et al (2020) and Singh et al (2019) stated that Financial Literacy has a positive and significant effect on Financial Behavior. In research conducted by Purwidianti et al (2022); Humairo & Sartika (2021) and Perwito et al (2020) show that Financial Literacy has a positive effect on Financial Behavior. These results are strengthened by research conducted by (Darwati et al, 2022); Dewi & Krisnawati (2020); Raut (2020) and Hamdani (2018) which prove that Financial Literacy has a significant effect on Financial Behavior.…”
Section: Introductionmentioning
confidence: 97%